Penerapan Visual Basic for Application (VBA) Sebagai Alat Bantu Ajar Enkripsi dan Dekripsi DES - Yasri Yasri (Bina Nusantara University, 2011)
The DES encryption/decryption algorithm is quite a popular algorithm due to ease in learning. Calculations for DES using binary numbers however are very difficult, including 16 rounds required for a full encode. Teaching DES encryption manually is difficult since it requires a long time. It also requires high accuracy for the 64-bit binary numbers, the possibility of mistakes are very high. Besides, the students cannot perform self-check, whether the given task is done correctly. Application of Excel and VBA is used to facilitate observation, comparison, and understanding the DES algorithm. The result is a teaching model using DES for modern encryption.